Family Strategies in Educating Children in the 5.0 Era: A Multicultural Islamic Education Perspective in Building a Generation of Character - Muthoifin; Ishmah Afiyah; Nuha; Lukman Yafi; Jihan Husna Srifyan (Walidem Institute and Publishing (WIP), 2024)
This study aims to explore family strategies in educating children in the 5.0 era from the perspective of multicultural Islamic education, focusing on efforts to build a generation with character. The 5.0 era is marked by rapid technological developments and digitalization, which affects family parenting and the value system taught to children. In the context of multicultural Islamic education, Islamic values and cultural diversity must be managed in harmony to produce a generation that is not only intellectually intelligent, but also has strong moral character, such as tolerance, empathy, and integrity. The research method used is a qualitative approach with a case study design. Data collection was carried out through in-depth interviews with families from diverse cultural backgrounds, observations, and analysis of documents related to children's education from the perspective of Islam and multiculturalism. The data obtained were analyzed thematically to understand the educational patterns applied in the family, as well as the challenges and solutions that emerged in educating children in the 5.0 era. The results of the study show that the family plays an important role in integrating religious and cultural values into children's education. The multicultural approach to Islamic education provides flexibility for families to instil universal values such as justice, togetherness, and respect for differences. In this case, technology is used as a supporting tool to reinforce learning, although prudent parental supervision is still needed. The originality of this research lies in the combination of the concept of Islamic and multicultural education in the context of the 5.0 era, which has not been explored in depth in academic studies. The implications of this study provide insight for educators and policymakers to design educational programs based on multicultural Islamic values, to build a resilient generation to face global challenges.